Emancipating early childhood literacy curricula: Pro-Black teaching in K-3 classrooms. (December 2022) - Braden, Eliza; Boutte, Gloria; Wynter-Hoyte, Kamania; Long, Susi; Aitken, Catharine; Collins, Saudah; Frazier, Jennipher; Gamble, Edith; Hall, Lindsay; Hodge, Stephanie; McDonald, Caitlyn; Merritt, Ashanda; et al.
The legacy of colonization includes stereotypes and misinformation about African and African descendant people as well as a void in an understanding the vast contributions of precolonial Africa to the world's knowledge impacting knowledge, languages, music, art, and sciences that we take for granted today. This misinformation remains pervasive throughout society perpetuated in schools by ensuring that curriculum is dominated by whiteness and lacks attention to the histories, heritages, communities, and languages of Black people. Pro-Black practices in response to centuries-old curricular voids and misinformation about Africa, the African Diaspora, and African descendant people can lead to an emancipatory education for all students. In our work, we draw on tenets of culturally relevant pedagogy and descriptions of Pro-Black pedagogy to describe the work of 13 early childhood educators who are committed to using their knowledge from ongoing professional development at one school in the southeastern United States. The work represented in this article reflects data collected over four years and analyzed in answer to the question: What are Pro-Black highlights of teaching in one school which sought to develop and normalize culturally relevant teaching including challenges to the work and efforts to negotiate those challenges? Data (e.g. student work, lesson plans, PD session PowerPoints, participants' responses to a questionnaire, informal commentaries throughout the PD process, and classroom observations) were collected and reviewed to develop this article. Recommendations are made for educators and scholars.